DOT1L Inhibition Sensitizes MLL-Rearranged AML to Chemotherapy - Liu, Wei (Public Library of Science, 2014)
DOT1L, the only known histone H3-lysine 79 (H3K79) methyltransferase, has been shown to be essential for the survival and proliferation of mixed-linkage leukemia (MLL) gene rearranged leukemia cells, which are often resistant to conventional chemotherapeutic agents. To study the functions of DOT1L in MLL-rearranged leukemia, SYC-522, a potent inhibitor of DOT1L developed in our laboratory, was used to treat MLL-rearranged leukemia cell lines and patient samples. SYC-522 significantly inhibited methylation at H3K79, but not H3K4 or H3K27, and decreased the expression of two important leukemia-relevant genes, HOXA9 and MEIS1, by more than 50%. It also significantly reduced the expression of CCND1 and BCL2L1, which are important regulators of cell cycle and anti-apoptotic signaling pathways. Exposure of MLL-rearranged leukemia cells to this compound caused cell cycle arrest and promoted differentiation of those cells, both morphologically and by increased CD14 expression. SYC-522 did not induce apoptosis, even at 10 µM for as long as 6 days. However, treatment with this DOT1L inhibitor decreased the colony formation ability of primary MLL-rearranged AML cells by up to 50%, and promoted monocytic differentiation. Notably, SYC-522 treatment significantly increased the sensitivity of MLL-rearranged leukemia cells to chemotherapeutics, such as mitoxantrone, etoposide and cytarabine. A similar sensitization was seen with primary MLL-rearranged AML cells. SYC-522 did not affect chemotherapy-induced apoptosis in leukemia cells without MLL-rearrangement. Suppression of DOT1L activity inhibited the mitoxantrone-induced increase in the DNA damage response marker, γH2AX, and increased the level of cPARP, an intracellular marker of apoptosis. These results demonstrated that SYC-522 selectively inhibited DOT1L, and thereby altered gene expression, promoted differentiation, and increased chemosensitivity by preventing DNA damage response. Therefore, inhibition of DOT1L, in combination with DNA damaging chemotherapy, represents a promising approach to improving outcomes for MLL-rearranged leukemia.